THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN PROMOTING SOCIAL TRANSFORMATION IN HIGHER EDUCATION - Rahanjamtel, Muhamad; Khozin, Nur; Hanafi, Hilaludin; Madia, Rusmin; Mariana, Mariana (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: Islamic Education holds a strategic position in shaping students’ moral character and ethical conduct, not merely through the transmission of Islamic teachings but also by internalizing spiritual values and ethical principles that influence social behavior. Purpose: Amid ongoing social transformations, including rapid technological development and cultural shifts, the significance of Islamic Education has become increasingly pronounced. Globalization and modernization bring both opportunities and challenges, such as moral decline, identity crises, and social tensions. Within this context, Islamic Education serves as a moral compass that enables students to navigate the complexities of contemporary society. Method: This study adopts a qualitative research design with a phenomenological approach, aiming to provide in-depth insights into enhancing the quality of Islamic Education instruction while emphasizing its role in addressing the dynamics of a continuously evolving social environment. Results: The findings reveal that Islamic Education plays a significant role in fostering students’ moral responsibility and social awareness, as well as equipping them to confront the challenges of the modern era. Moreover, the integration of contemporary pedagogical strategies with traditional Islamic teachings enhances the effectiveness of Islamic Education in character formation amid rapid social change.